POST-TAX CHANGE RATES: PERCEPTIONS OF MSME IN BREBES DISTRICT IN TAX RATES - Ghea Dwi Rahmadiane (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2022)
The phenomenon in Indonesia regarding the level of taxpayer compliance is still relatively low when compared to the growth in the number of businesses. This research aims at determining the perception of taxpayers of micro, small and medium enterprises after changes in tax rates government regulation. This research method used was descriptive qualitative statistical analysis. The population used was MSMEs in Brebes District, and the sample taken is 5 MSMEs that could represent each business field with a simple random sampling technique. The respondents used in this research were MSMEs in Brebes District which experienced a decrease in income and get more comprehensive information on the latest tax regulations. The conclusion from this research was that MSME actors objected to the tax rate of 1% of turnover. MSME actors were represented by respondents who appreciated the new tax rate of 0.5% of the turnover contained in PP No. 23 of 2018.